2009
DOI: 10.9775/kvfd.2010.2376
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Long and Short Term Applications of Progestogen Containing Vaginal Sponges and Subcutaneus Implants on Fertility During Breeding Season in Damascus Goats

Abstract: ÖzetÇalışma; üreme sezonunda Şami ırkı keçilerde, fluorogeston asetat (FGA) içeren vaginal sünger ve norgestomet içeren kulak altı implantların uzun ve kısa süreli kullanımlarının fertilite parametreleri üzerindeki etkilerinin belirlenmesi amacıyla düzenlendi. Araştırmada; sağlıklı, en az bir doğum yapmış, yaşları 3 ile 6 arasında değişen 88 Şami keçisi kullanıldı. Keçiler uzun süreli sünger (USS, n=22), kısa süreli sünger (KSS, n=22), uzun süreli implant (USİ, n=22) ve kısa süreli implant (KSİ, n=22) olmak üz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Synchronization of estrus in female goats has been achieved through administration of progesterone or its synthetic analogues, with a vaginal device or a subcutaneous auricular implant [19][20][21][22] . The combination of equine chorionic gonadotropin (eCG), prostaglandin F2α (PGF2α) and progestagen treatments eliminates variability in goats' ovulatory response, increases production of ovulatory follicles and ovulation rate, and improves fertility 19,[22][23][24] . İnce and Köker 25 reported that treatment with progestagen in conjunction with PGF2α and eCG was convenient for estrous synchronization of Turkish Saanen goats during the breeding season in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronization of estrus in female goats has been achieved through administration of progesterone or its synthetic analogues, with a vaginal device or a subcutaneous auricular implant [19][20][21][22] . The combination of equine chorionic gonadotropin (eCG), prostaglandin F2α (PGF2α) and progestagen treatments eliminates variability in goats' ovulatory response, increases production of ovulatory follicles and ovulation rate, and improves fertility 19,[22][23][24] . İnce and Köker 25 reported that treatment with progestagen in conjunction with PGF2α and eCG was convenient for estrous synchronization of Turkish Saanen goats during the breeding season in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…The body weights of does were 48.5 ± 8.11 kg (means±SD). Oestrus was induced and synchronized using the method by Özer and Doğruer (2011). Pregnancy tests were carried out on the 45 th day of pregnancy using a real-time ultrasonography device (Pie Medical, Falco, The Netherlands) equipped with a 5-7,5 MHz linear rectal probe transrectally after completion of the matings.…”
Section: Animalsmentioning
confidence: 99%